Prevalence of Inappropriate Antibiotic Prescriptions Among US Ambulatory Care Visits, 2010–2011. Issue 9 (September 2016) - Fleming-Dutra, Katherine E.; Hersh, Adam L.; Shapiro, Daniel J.; Bartoces, Monina; Enns, Eva A.; File, Thomas M.; Finkelstein, Jonathan A.; Gerber, Jeffrey S.; Hyun, David Y.; Linder, Jeffrey A.; Lynfield, Ruth; Margolis, David J.; et al.
Abstract : (Abstracted from JAMA 2016;315(17):1864–1873) Antibiotic-resistant infections, driven by inappropriate outpatient antibiotic use, are widespread in the United States. A number of initiatives, including the Centers for Disease Control and Prevention's (CDC's) Get Smart: Know When Antibiotics Work, the National Action Plan for Combating Antibiotic-Resistant Bacteria, and Healthcare Effectiveness Data and Information Set (HEDIS) have been undertaken to promote appropriate outpatient antibiotic use; however, the fraction that is inappropriate and has to be reduced is not known.